Fault Tolerant Control Design for Linear Systems with Appropriate Performance Degradation Using Eigen Structure Assignment - S. Kanthalakshmi; M. Raghappriya; R. Latha (Advanced Aspects of Engineering Research Vol. 10, 2021)
The main goal is to design a fault-tolerant control with acceptable performance degradation due to faults in actuators, sensors, and device dynamics using multiple model techniques. The achievable performance under various component failures is expressed in the form of reference models, also known as appropriate performance reference models. Using eigen structure assignment, a series of controllers is synthesised based on these models. To achieve desired output, the proper controller is reconfigured for a particular fault state, and revised command input is selected automatically. The fault detection and diagnosis is done using IMM estimator and the controller reconfiguration is done using eigen structure assignment. The aircraft model is chosen to demonstrate the effectiveness of the model.